The influence of material defects on the forming ability of sheet metal - Bressan J.D.* (1997)
A relevant aspect of sheet forming is the analysis of the influence of material imperfections on the forming ability. These imperfections can be defined as local variations in thickness and in plastic properties which can affect the plastic flow and therefore, influence the neck formation phenomena. From the microstructural point of view this could be due to the variations in grain size and orientation, inclusions and second-phase contents, porosity, as well as residual cold work, originating from the melting, solidification and rolling processes. As a consequence of these imperfections within the material, the thickness, strain hardening, strain-rate sensitivity and strength coefficients and initial prestrain may exhibit local variations and thereby the initiation of the neck and the limit strains can be influenced. Using the concept of a strain gradient at the neck, the limiting strains are investigated with respect to the material parameters mentioned above. The role of these defects on the development of the local neck and the forming-limit diagram (FLD) are discussed. © 1997 Elsevier Science S.A.